On Anthropologists or the Extent to Which Anthropology is a Collection of Intellectual Career - Ivan Kovačević (University of Belgrade, 2016)
Anthropologists who can be categorized as "internalists" engage with the self in two completely different ways. Ethnographers with an anthropological diploma arrived at auto-ethnography through reflexivity, while those who deal with the self at the disciplinary level usually write about anthropology or, most often, write histories of anthropology. Anthropologists categorized as "externalist" engage with the world at large. Some of them are classic ethnographers who produce ordinary or "thick" descriptions, some of them try to interpret the world, and the third kind arrive at militant anthropology by way of activist anthropology, and try to change the world in accordance with their political opinion.